The Book of Laughter and Forgetting - Kundera, Milan (New York Harper, 1999)
In seven wonderfully integrated parts, different aspects of human existence are magnified and reduced, reordered and emphasized, newly examined, analyzed, and experienced. [This novel] is part fairy tale, part literary criticism, part political tract, part musicology, and part autobiography.-http://www.booksinprint.com.
Include Notes
Keywords: Black Humor -- Czech Literature